Does Early Algebra Matter? The Effectiveness of an Early Algebra Intervention in Grades 3 to 5. (October 2019) - Blanton, Maria; Stroud, Rena; Stephens, Ana; Gardiner, Angela Murphy; Stylianou, Despina A.; Knuth, Eric; Isler-Baykal, Isil; Strachota, Susanne
A cluster randomized trial design was used to examine the effectiveness of a Grades 3 to 5 early algebra intervention with a diverse student population. Forty-six schools in three school districts participated. Students in treatment schools were taught the intervention by classroom teachers during regular mathematics instruction. Students in control schools received only regular mathematics instruction. Using a three-level longitudinal piecewise hierarchical linear model, the study explored the impact of the intervention in terms of both performance (correctness) and strategy use in students' responses to written algebra assessments. Results show that during Grade 3, treatment students, including those in at-risk settings, improved at a significantly faster rate than control students on both outcome measures and maintained their advantage throughout the intervention.